PENGEMBANGAN MEDIA KARTU GAMBAR ASOSIATIF PADA PEMBELAJARAN HURUF KATAKANA - Mardila Noviyanti; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This research is about development of associative picture card katakana to overcome the dificullties in memorizing katakana latters .The learning media of katakana letters which is development is suitable for beginners. The assosiative picture card media used a tehcnique based on a picture , so it is easy to understand as Levie a& Levie in Arsyad (1996: 9) states that learning through picture stimulus and later stimulus can make learning outcome be better for memorizing ,identifying, recalling, and connecting facty and concept. This research use a “ research and development “.The method of this development and research is use a Sugiyono design, but this research and development only adapted five sugiono’s Model research and development Among others : 1) incorporation data, 2) planning, 3)basic product development, 4) validation (validator), 5) basic step product revision. The incorporation data method used is with distributing necessity questionnaire validation and The result of the validation of expert declared to be used as a presentation media with an average of 87,5 %, validation of subject matter expert 1 declared valid to be used as a presentation an average of 79,5 %, and the validation research by the subject matter expert 2 got a presentation 75 %. From the research of the validation all of the expert and subject matter expert it can be conclude that it was visible to be used in learning katakana.Key words : Associative Picture Card , Research And Development, Katakana